The Place and Role of The Subject "Safety of Life Activities" In the Preparation of Future Environmental Engineers for Professional Activity (Eurasian Journal of Research, Development and Innovation, 2024)
In this work, the issues of forming a stable interest in life safety and labor protection activities among future environmental engineers who are trained in technical higher education institutions were considered.